Hub height optimisation of commercial WTGs based on accurate wind resource analysis. Issue 1 (February 2022) - Roberts, Kyle O; Mahomed, Nawaz
Wind turbine selection and optimal hub height positioning are crucial elements of wind power projects. However, in higher class wind speeds especially, over-exposure of wind turbines can lead to a reduction in power generation capacity. In this study, wind measurements from a met mast were validated according to specifications issued by IRENA and NREL. As a first step, it is shown that commercial WTGs from a database may be matched to the wind class and turbulence intensity. Secondly, a wind turbine selection algorithm, based on maximisation of capacity factor, was implemented across the range of WTGs. The selected WTGs were further exposed to an iterative algorithm using pointwise air density and wind shear coefficients. It is shown that a unique maximum capacity factor, and hence wind power generation, exists for a wind turbine, premised on its eventual over-exposure to the wind resource above a certain hub height.